Eccentric hamstring strength and asymmetry in female handball athletes: A descriptive study - Alvito Dandy Putra Sanjaya; Awang Firmansyah; Aziz Abdul Hakim; Panji Bana (CV Rezki Media, 2025)
Background: Handball is a competitive sport that requires high physical strength and muscle endurance. The game requires a balance of muscle strength to support athletes in performing movements such as sprints, jumps, and fast movement maneuvers. Lack of flexibility and high hamstring muscle asymmetry values ​​are risk factors for injury to handball athletes. Objectives: This study aims to determine the eccentric strength and hamstring muscle asymmetry in female handball athletes in Surabaya City. Methods: The study subjects were 13 female handball athletes from Surabaya aged 18-23 years with regional-level competition experience and no lower extremity injuries. The instrument in this study is Nordbord by Vald Performance; Nordbord is a portable rapid assessment tool that can analyze large groups, providing information about the exact functional strength parameters quickly and efficiently. This study used a quantitative descriptive method to analyze hamstring muscle strength and asymmetry data. Results: Indicated the athletes had an average (body mass of 59.30 ± 10.94 kg and height of 164.80 ± 6.80 cm). The overall eccentric hamstring strength was 88.1% of the expected norm, with right and left maximum forces averaging 230.70 ± 48.80 N and 233.61 ± 50.15 N, respectively. The average asymmetry between legs was -1.44 ± 9.14%, suggesting relatively balanced muscle strength. Conclusions: The study concluded that hamstring eccentric strength in both legs should be improved by approximately 11.9% while maintaining the current low asymmetry levels to support muscle balance. Targeted training interventions are recommended to increase hamstring strength and minimize asymmetry, enhancing performance and reducing injury risk in female handball athletes.